Dispersion-engineered spin photonics based on folded-path metasurfaces - Fei Zhang; Hanlin Bao; Mingbo Pu; Yinghui Guo; Tongtong Kang; Xiong Li; Qiong He; Mingfeng Xu; Xiaoliang Ma; Xiangang Luo (Light: Science & Applications)
Abstract Spin photonics revolutionizes photonic technology by enabling precise manipulation of photon spin states, with spin-decoupled metasurfaces emerging as pivotal in complex optical field manipulation. Here, we propose a folded-path metasurface concept that enables independent dispersion and phase control of two opposite spin states, effectively overcoming the limitations of spin photonics in achieving broadband decoupling and higher integration levels. This advanced dispersion engineering is achieved by modifying the equivalent length of a folded path, generated by a virtual reflective surface, in contrast to previous methods that depended on effective refractive index control by altering structural geometries. Our approach unlocks previously unattainable capabilities, such as achieving achromatic focusing and achromatic spin Hall effect using the rotational degree of freedom, and generating spatiotemporal vector optical fields with only a single metasurface. This advancement substantially broadens the potential of metasurface-based spin photonics, extending its applications from the spatial domain to the spatiotemporal domain.